Variabilidade da região ITS do Cluster Ribossõnico Nuclear em populações de ostras de três estuários da costa cearense - Vasconcelos, Régis Fernandes (2009)
Oyster taxonomic classifications are problematic, because these organisms have few informative morphological characteristics. The oyster C.brasiliana was, for decades, confused with C. rhizophorae. However, recent studies indicate that the two species are biologically distinct. In order to help solving systematic issues among mollusks the nuclear ribosomal ITS region has been often used in phylogenetic and taxonomic studies. ITS presents high variability and relatively easy amplification by thermocycling. The present study aimed at examining the variability of the ITS-1 region of oyster populations of C.rhizophorae in three estuaries from Ceará State, as well as investigating the presence of a second Crassostrea species in the region. Individuals of the native oyster C.cf.rhizophorae were collected in the estuaries of Ceará for analysis of population variability. We also collected individuals of C.cf.brasiliana for study of phylogeny and evaluation of taxonomic status. After DNA extraction and ITS-1 amplification, sequences were obtained for phylogenetic and population analysis. In addition to these sequences, 35 ITS-1 sequences were retrieved from GenBank, representing 12 species of Crassostrea oysters. Two additional sequences of Saccostrea glomerata were used as outgroup. Phylogenetic trees were inferred through neighbor-joining and maximum parsimony methods. Intraspecific variability in C.cf.rhizophorae was studied through a nested clade maximum parsimony method. Complete ITS-1 sequences were obtained for C.brasiliana and C.rhizophorae with 427 and 439 bp, respectively. The neighbor-joining tree showed a clear separation between C.cf.brasiliana and C.cf.rhizophorae branches (100% bootstrap support), confirming the occurrence of at least two species of Crassostrea in Ceará. Although C. brasiliana has been considered synonymous with C.virginica, the results presented here indicate that C.virginica is much closer to C.rhizophorae The same basic topology was observed in the maximum parsimony tree. That tree also showed a clear separation between C.cf.brasiliana and C.cf.rhizophorae branches (100% bootstrap support). Maximum parsimony analysis of intraspecific variability of C.cf.rhizophorae for the three estuaries studied showed 7 different sequences for C.cf.rhizophorae. The network between these sequences suggests the presence of limited gene flow between populations. ITS-1 seems to be ideal for studies of phylogeny of oysters and has shown to be informative for population studies as well. The confirmation of the presence of a second species of oysters belonging to the genus Crassostrea in Ceará will have direct consequences in the management of these resources, which have marked ecological, economic and social importance to our state.